Pengaruh Intensitas Perhatian Orang Tua dan Motivasi Belajar Terhadap Prestasi Belajar Pada Siswa Kelas Tinggi SD Negeri 3 Ngerangan Klaten Tahun Ajaran 2015/2016 - Arsyada, Naqi, Drs. Suwarno, SH., M. Pd (2016)
Naqi Arsyada /A 510120066. INFLUENCE THE INTENSITY OF PARENTAL ATTENTION AND LEARNING MOTIVATION TOWARD HIGH GRADE STUDENT SD NEGERI 3 NGERANGAN KLATEN ACADEMIC YEAR 2015/2016. Research Paper. Faculty of Teacher Training and Science Education, University of Muhammadiyah Surakarta. April, 2016. Factors that affect student achievement, one factor is the intensity of attention from their parents. Another factor that can affect student achievement is the motivation to learn. The purpose of this study was to: (1) Determine the influence the intensity of the attention of parents to the student achievement in high grade students of SD Negeri 3 Ngerangan Klaten academic year 2015/2016. (2) Determine the influence learning motivation towards learning achievement in high grade students of SD Negeri 3 Ngerangan Klaten academic year 2015/2016. (3) Determine the influence the intensity of parental attention and learning motivation on learning achievement in high grade students of SD Negeri 3 Ngerangan Klaten academic year 2015/2016. (4) Determine the effective contribution of the intensity of parental attention and learning motivation on learning achievement in high grade of SD Negeri 3 Ngerangan Klaten academic year 2015/2016. This research includes quantitative research. The population in this study were 50 students of SD Negeri 3 Ngerangan Klaten. The sample in this study were 50 students of class IV and V. Data collection techniques in this study was a questionnaire and documentation. Data analysis technique used is multiple linear regression analysis, t test, F test, the coefficient of determination, SR and SE. Based on the results of multiple linear regression equation Y = 52.970 + 0.132 X1 + 0.165 X2. The results of data analysis the significance level of 0.05 was obtained: (1) There is the influence of the intensity of the attention of parents to the student achievement. This is based on test results t is known that tcount> ttable, namely 2.337> 2.011 and the significance value <0.05 (0.024 <0.05). (2) There is an effect of learning motivation on learning achievement. This is based on test results t is known that tcount> ttable, namely 3.023> 2.011 and the significance value <0.05 (0.004 <0.05. (3) There is the influence the intensity of parental attention and learning motivation on learning achievement. It is based on test F is known that Fhitung> Ftable is 17,216> 3.15 and a significance value <0.05 is (0.000 <0.05). From the results of determination (R²) obtained the results for 0.423 show that the influence of the intensity of parental attention and learning motivation the learning achievement is 42.3%, while the remaining 57.7% is influenced by other factors, including the discipline of learning, interest, intelligence, environment, learning, and others. Keywords: intensity of parental attention, motivation and learning achievement.